Analysis of Public Service Performance at the Regional Revenue Agency (BAPENDA) of Bengkulu City - Sitanggang, Sintiani O.; Hakim, Kahar; Nursanty (Future Science, 2024)
This article presents an analysis of public service performance at the Badan Pendapatan Daerah (Bapenda) of Bengkulu City, focusing on the collection of motor vehicle taxes and vehicle title transfer fees in 2023. In the context of this study, the effectiveness of Bapenda is analyzed across three aspects: production, quality, and efficiency, and is also examined from the dimensions of flexibility and employee satisfaction. The research method employs a descriptive-analytical approach by collecting data through observation, interviews, and analysis of related documents. The analysis results indicate that the effectiveness of Bapenda in managing regional revenue is still not optimal, particularly in terms of achieving revenue targets, service quality, and expenditure management efficiency. Although efforts have been made to verify the accountability of APBD implementation, errors in financial management by organizational units are still found. Based on these findings, it is concluded that Bapenda needs improvements in various aspects to enhance its effectiveness, including better coordination among units, increased understanding of applicable regulations, and improved employee satisfaction in performing verification tasks. The implications of this study highlight the importance of strengthening internal supervision and control in regional financial management to improve overall public service performance.